ChemInform Abstract: Rauhut—Currier Reaction of Nitroalkenes with Vinyl Sulfones. Issue 36 (15th August 2013) - Kumar, Rahul; Kumar, Tarun; Mobin, Shaikh M.; Nambothiri, Irishi N. N.
Abstract The title reaction with the vinyl bis‐sulfone (I) allows a new and efficient access to sulfonylated nitroalkenes of type (III).